After competitive authoritarianism hybrid regime legacies and the quality of democracy in Croatia. Issue 4 (2nd October 2019) - Castaldo, Antonino; Pinna, Alessandra
ABSTRACT: The impact of 'authoritarian legacies' on successor democracies has been widely researched with reference to every type of non-democratic regime. However, scant attention has been devoted to hybrid regimes legacies, despite the growing relevance acquired by these regimes in the last decades. This paper deals with the legacies of Levitsky and Way's Competitive Authoritarian model, evaluating their impact on successor democracies through an analysis of the Croatian case. The research shows that the legacies of the Tuđman's regime significantly affected the Quality of Democracy in Croatia. The innovative capacity of the former regime and the continuous nature of the transition explain this relevant impact, only partially moderated by the influence of important international actors (EU).